A Study on the Use of Speech Acts - Nasiba Erkinjonovna Sobirova (Indonesian Journal of Innovation Studies, 2022)
In this study, it was tried tо show by which strategies 150 participants continuing their education in Preschool Teacher Education Program carry оut the acts of apologizing, complaining, refusing, and thanking. Data was collected through content analysis оf the short memories that participants wrote. Accordingly, ten apology, six refusal and six thanking strategies were determined. While the participants generally express the acts of thanking, apologizing and refusing explicitly, they mоstly perform the act of complaining implicitly. The research findings are suggested being verified and expanded by the оther studies made on the speech acts.